1998
DOI: 10.1007/s002449900289
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal, Organochlorine Pesticide, and PCB Residues in Eggs and Feathers of Herons Breeding in Northern Italy

Abstract: We report on organochlorine pesticide and PCB concentrations in eggs of the little egret, Egretta garzetta, and the black-crowned night-heron, Nycticorax nycticorax, collected in 1993-1994, and on mercury, cadmium, and lead concentrations in feathers of 20-day-old nestlings collected from the same nests in 1994, from heronries near Pavia, northern Italy. Organochlorine pesticide and PCB residues were lower than those commonly associated with mortality and reduced reproductive success. As population levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
3
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 55 publications
4
29
3
4
Order By: Relevance
“…Little blue heron chicks sequestered on average 1.01 ppm lead and 0.47 ppm cadmium in their feathers (Spahn and Sherry 1999). Fasola et al (1998) detected lead levels in feathers of heron chicks up to 4.5 ppm and cadmium levels up to 0.64 ppm. The cadmium concentrations reported in our study are considerably lower than those reported in other studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Little blue heron chicks sequestered on average 1.01 ppm lead and 0.47 ppm cadmium in their feathers (Spahn and Sherry 1999). Fasola et al (1998) detected lead levels in feathers of heron chicks up to 4.5 ppm and cadmium levels up to 0.64 ppm. The cadmium concentrations reported in our study are considerably lower than those reported in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies, which focused mainly on seabirds Gochfeld 1993, 1995;Burger 1996) and herons (Fasola et al 1998;Spahn and Sherry 1999), have reported detectable levels of lead and cadmium in feathers of nestling birds. Burger (1993) reported lead and cadmium levels in feathers of nestling Franklin's gulls (Larus pipixcan) of 0.8 and 0.21 ppm, respectively, while feathers of roseate tern (Sterna dougallii) and black skimmer (Rynchops niger) chicks accumulated up to 0.5 and 4.1 ppm respectively (Burger and Gochfeld 1993).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the ease with which waterbirds can be used to obtain important information about wetland ecosystems, their possible role as early warning indicators for regime shifts sensu Carpenter et al (2011) remains an area for future research. Waterbird feathers and other tissues can also be very useful as biomonitors of heavy metals and other contaminants (Fasola, Movalli & Gandini, 1998;Taggart et al, 2006;Burger & Eichhorst, 2007).…”
Section: (2) Bioindicatorsmentioning
confidence: 99%
“…''Different species of birds such as herons and egrets have been used as a bio-indicator and/or bio-monitor of local environmental contamination because they are high on the food-chain, exposed to a wide range of chemicals, susceptible to bioaccumulation and are geographically widespread'' (Burger 1994(Burger , 1995Scheifler et al 2006;Burger et al 2007;Deng et al 2007;Horai et al 2007). Various studies have evaluated heavy metal accumulation in different body organs (Elliott and Scheuhammeri 1997;Mateo and Guitart 2003;Deng et al 2007;Horai et al 2007;Kojadinovic et al 2007), blood (Scheifler et al 2006), eggs (Fasola et al 1998;Burger and Gochfeld 2004), eggshells (Ayas 2007), feathers (Fasola et al 1998;Movalli 2000) and prey samples (Zhang et al 2006) of different bird species. Studies using predatory migratory and non-migratory bird species provided valuable information on spatial and temporal trends of heavy metals (Burger and Gochfeld 2004).…”
Section: Introductionmentioning
confidence: 99%